Prevalence of Smoking among Secondary School Students and its Associated Factors in the District of Kuantan, Malaysia - Osman, Azlan (2007)

(untitled)
The aims of this study were firstly to determine the prevalence of smoking and factors associated with smoking, and secondly to determine the knowledge, attitudes and practices among secondary school in the District of Kuantan, Malaysia. A cross-sectional study design was used. A stratified proportionate and random size sampling technique was used to select the sample. The lists of 29 selected schools with a population of 10,983 students are registered under the District of Kuantan Education Department served as the sampling frame. By using formula in Krejcie & Morgan (1970), for determining sample a total of 1036 samples was used. Data was collected commencing July 2005 t hrough using a structured pre test and actual test questionnaire. The response rate was 86.9%. Out of 900 respondents, 55.4% are males’ students and 44.6% are females’ students with 94.9% of them being Malays (Muslim). More ever 33.4% of respondents were in Form 1, 33.2% were in Form 2 and 33.4% were Form 3 students. The overall prevalence of smoking is 43%; with males’ and females’ proportions at 63.5% and 17.5% respectively. Among the three forms, the Form 3 with 18.6% represents the highest percentage of smoking. The main reason for male students to start smoking is the influence of friends with 60.3% and females 35.7%. Waiting for the bus (32.4%) was the most common occasion for smoking. The prevalence of smoking was significantly associated with age, economic status, race, religions, and family and peer groups smoking habits. Most students had average knowledge on the health risk of smoking. Females and non-smoker had better knowledge on hazards of smoking and possed more positive attitudes. In conclusion, smoking prevalence of school students from the district of Kuantan, Malaysia is low in comparison with the national prevalence. However, It stills constitutes a problem among secondary students in spite of their knowledge of its hazard, attitudes and practices. There is a need to implement an antismoking program for secondary school students.